(untitled) (Progressive Agriculture, 2014)
The myiasis is very common surgical affections of ruminants in Bangladesh. There are limited researches on the maggot wound infestation in Bangladesh. A retrospective study was performed to collect data and to get a clear and genuine concept on myiasis affections in ruminants in respect to species. age, sex, breed, season and predilection sites. The present study was conducted in Veterinary Clinic, Bangladesh Agricultural University, Mymensingh and data was recorded from 2008 to 2012. Results showed that 151 animals were affected with myiasis and maggot wounds predominantly occurred in the cattle (71.6%) among which calves were more affected. Myiasis was very prone to occur in the navel, vulva, leg and ear. During the study period, more affection occurred in animals of below 6 months (41%). The females (66%) were more frequently affected than the males (34%) and cross breed (57%) was more affected compared to local breed (43%).Moreover, infestation frequently observed from March to June (80%). This study could help veterinarians as well as farmers to be aware of the occurrence of maggot wounds and to implement protective measures with minimum complications. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19110 Progress. Agric. 24(1&2): 101 - 106, 2013